MOTIVASI BELAJAR LANSIA DALAM MENGIKUTI PENGAJIAN RUTIN AHADAN DI MAJELIS TAKLIM DARUSSALAM KUNIR - Ahmad Farihin; Septian Eka Prahardik; Ahmad Dasuki; Riema Afriani Kusumadewi; Putri Anggraeni (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2021)
Old age is a period in which a person experiences changes in the dimensions he has; physical, psychological, spiritual, social, and potential dimensions. Ideally old age is filled with maturity that is stable at the changes experienced. However, the elderly will be faced with the problem of situational limitations both internally and externally. Following routine recitations is one of the activities that can cover the needs of solving problems in the elderly. This study uses a qualitative research method with a descriptive approach that seeks to explore in depth the motivation of the elderly in participating in routine recitation activities. Data collection techniques were carried out by intense interviews and direct field observations. The results of this study indicate that the motivation of the elderly to attend regular recitations is the fulfillment of learning and educational needs, the motivation of the elderly in attending routine recitations meets two aspects of motivation; component of values and components of hope, so it can be concluded that the elderly who are recitation participants are elderly who care about the future because they meet 4 of 5 indicators of elderly who care about the future. The supporting factors for the elderly in attending the recitation consist of internal and external factors. The level of motivation of the elderly in attending regular recitations is included in the category of inner motivation level (motivation that comes from inner strength) which is the highest level of motivation.